The complete AvrII restriction map of the Escherichia coli genome and comparisons of several laboratory strains. - Daniels, D L (1990)
The complete 13 site AvrII restriction map of the genome of E coli strain MG1655 is presented and compared with several other E. coli strains. The map was determined primarily by isolating individual AvrII fragments from pulsed-field gels, and hybridizing these large probes to a battery of mapped E. coli clones in lambda vectors. AvrII restriction patterns for eight other laboratory strains were determined and maps for seven of them deduced from the gel and comparisons between the strain genotypes, the MG1655 map, and AvrII sites in E. coli sequences taken from Genbank.